Self-healing polyurethane-elastomer with mechanical tunability for multiple biomedical applications in vivo - Chenyu Jiang (Nature Portfolio, 2021)
The unique properties of self-healing materials hold great potential in the field of biomedical engineering. Here, the authors designed a series of biodegradable and biocompatible self-healing elastomers with tunable mechanical properties, and apply them to various disease models in vivo, including aortic aneurism, bone fracture and nerve amputation.